Pemanfaatan Bahan Ajar dalam Peningkatan Motivasi Belajar Siswa di Madrasah - Setiawan, Nandang (Center for Religious Studies and Social Empowerment Foundation, 2023)
Utilizing teaching materials that suit student characteristics and learning materials will increase student motivation. Teachers are required to be able to utilize existing teaching materials in accordance with the latest developments in science and technology. This article reveals the use of teaching materials by teachers in increasing students' learning motivation at Madrasah Tsanawiyah Al-Baqiyatush Shabayar Kuala Tungkal Jambi. The focus of the research is how to implement the use of teaching materials in the learning process at this Islamic boarding school in order to increase student learning motivation? This article comes from field research with a qualitative research approach. Data collection was carried out using observation, interviews and documentation techniques. The research results show that the use of teaching materials in the learning process at this Islamic boarding school is almost applied in all subjects. Teachers are also aware that teaching materials are learning resources which currently play a very important role in supporting the learning process. Pemanfaatan bahan ajar yang sesuai dengan karakteristik siswa dan materi pembelajaran akan meningkatkan motivasi peserta didik. Guru dituntut untuk dapat memanfaatkan bahan ajar yang ada sesuai dengan perkembangan ilmu pengetahuan dan teknologi terkini. Artikel ini mengungkap pemanfaatan bahan ajar oleh guru dalam meningkatkan motivasi belajar siswa di Madrasah Tsanawiyah Al-Baqiyatush Shalihat Kuala Tungkal Jambi. Fokus penelitian adalah bagaimana implementasi penggunaan bahan ajar dalam proses pembelajaran pada pesantren ini dalam rangka meningkatkan motivasi belajar siswa? Artikel ini berasal dari penelitian lapangan dengan pendekatan penelitian kualitatif. Pengumpulan data dilakukan dengan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penggunaan bahan ajar dalam proses pembelajaran pada pesantren ini hampir diterapkan dalam semua mata pelajaran. Para guru juga sadar bahwa bahan ajar adalah sumber belajar yang sampai saat ini sangat berperan penting untuk menunjang proses pembelajaran.